2001
DOI: 10.1161/01.cir.103.11.1585
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy Decreases Slowly but Not Rapidly Activating Delayed Rectifier Potassium Currents of Epicardial and Endocardial Myocytes in Rabbits

Abstract: LVH induces a decrease in I(Ks) density and increases the propensity to develop early afterdepolarizations, especially in Endo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 29 publications
3
65
0
Order By: Relevance
“…A preliminary study (18) has reported that I Ks was reduced in cells from terminally failing human hearts compared with mildly diseased cells. In the present study, we found that I Ks , and not I Kr , was significantly reduced in all three regions, consistent with a recent report (48) in hypertrophic rabbit hearts in which only I Ks , not I Kr , was reduced in ventricular endocardial and epicardial cells. Our results showed that the percentage of I Ks reduction was greater in epicardial and endocardial cells than in midmyocardial cells, which may contribute in part to the inhomogeneous prolongation of APD in the three regions.…”
Section: Discussionsupporting
confidence: 93%
“…A preliminary study (18) has reported that I Ks was reduced in cells from terminally failing human hearts compared with mildly diseased cells. In the present study, we found that I Ks , and not I Kr , was significantly reduced in all three regions, consistent with a recent report (48) in hypertrophic rabbit hearts in which only I Ks , not I Kr , was reduced in ventricular endocardial and epicardial cells. Our results showed that the percentage of I Ks reduction was greater in epicardial and endocardial cells than in midmyocardial cells, which may contribute in part to the inhomogeneous prolongation of APD in the three regions.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, transmural heterogeneities in ionic currents have been incorporated based on rabbit experimental data (McIntosh et al, 1998(McIntosh et al, , 2000Xu et al, 2001), as done in a previous simulation study (Saucerman et al, 2004). Consistent with previous research (McIntosh et al, 1998(McIntosh et al, , 2000Viswanathan et al, 1999;Xu et al, 2001;Gima and Rudy, 2002;Idriss and Wolf, 2004;Saucerman et al, 2004;Sampson and Henriquez, 2005), our study shows that the transmural differences in ionic currents result in differences in the shape and duration of the action potential in epicardial, midmyocardial and endocardial cells. In isolated single cells, the presence of a prominent I to current in epicardial and midmycardial myocytes gives rise to a notch following the upstroke of the action potential, which is absent in endocardial action potentials (Fig.…”
Section: Transmural Electrophysiological Heterogeneities In the Ventrsupporting
confidence: 78%
“…Experimental studies using isolated endocardial, midmyocardial and epicardial myocytes report transmural differences in I to in canine, rabbit, guinea pig and human (Li et al, 1998;McIntosh et al, 1998;Antzelevitch et al, 1999a, b), in I Na in canine (Antzelevitch et al, 1999a, b), in I Ks in canine and rabbit (Liu and Antzelevitch, 1995;Xu et al, 2001;Yan et al, 2001), and to a smaller extent, in I Kr in rabbit ). In our study, transmural heterogeneities in ionic currents have been incorporated based on rabbit experimental data (McIntosh et al, 1998(McIntosh et al, , 2000Xu et al, 2001), as done in a previous simulation study (Saucerman et al, 2004).…”
Section: Transmural Electrophysiological Heterogeneities In the Ventrmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors, such as sex, 30,63,64 body mass index, 65,66 myocardial ischemia, 67,68 heart failure, 69,70 hypothermia, 71 and hypokalemia, 72,73 have been correlated with prolonged QT intervals in other studies.…”
Section: Risk Factors and Alqtsmentioning
confidence: 93%